Analysis of the Ability of Number Sense of Elementary School Grade V Students In Understanding The Concept of Fractional Numbers - I Gusti Agung Shomia Anjali; Subanji Subanji; Intan Sari Rufiana (Eduvest - Journal of Universal Studies, 2025)
The importance of number sense in helping students learn mathematics is listed in the achievement of elementary school mathematics learning in the number element in each phase. Individual number sense abilities vary, influenced by their level of education, learning experience, and mathematical ability, whether high, medium, or low. The purpose of this study is to analyze and describe the number sense ability of grade V students of SDK Marsudisiwi by considering mathematical ability. The research method used is descriptive qualitative research. Three students were selected as research subjects, each representing the student's math ability category, namely the high, medium, and low categories. The data collection technique was carried out by written test, interview, and documentation methods. Data analysis was carried out by reduction, presentation, and drawing conclusions. The results of the analysis showed that students with various levels of mathematical ability had the ability to evaluate the fairness of the calculation results. Although students with high and moderate mathematical ability can identify the characteristics of the results of number operations, they, along with students with low ability, have not been able to establish the closest approximate estimates for the results of number operations and present them, nor have they been able to determine the sequential nature of number results and their regularity in the number system.